Psychological Impact and Anxiety in Pregnant Women During the COVID-19 Pandemic in the Southeastern Region of Bangladesh (Journal of Medicine, 2025)
Introduction:The COVID-19 Pandemic has had a profound effect on the psychology of people around the world. It posed fear and anxiety to all, and pregnant women became more vulnerable. Various factors and the scarcity of treatment and hospital facilities during the lockdown worsened the mental state. Aim:The study was performed to assess pregnant women's psychological impact and anxiety during the COVID-19 pandemic using a preset validated questionnaire.Methodology:This cross-sectional study was conducted among 553 pregnant women, who visited for antenatal care in the outpatient department of Obstetrics and Gynecology, Chittagong Medical College Hospital, and private chambers of researchers from October to December 2020.The psychological impact of the COVID-19 pandemic on pregnant women was assessed by the Italian version of the Impact of Event Scale (IES-R) questionnaire. A score of >24 was taken as significant. A six-item short-form of the Spielberger State-Trait Anxiety Inventory (STAI-6) scale was used to measure anxiety, and a score >36 was considered significant. Data were analyzed with SPSS-22 using the Chi-square test (for categorical data) and t-test (for numerical data) as appropriate. The NOVA test was done to calculate the significance between the groups. The P values 36) [40.50 (± 15.027)] (range: 5-77). Severe IES-R scores were observed in women who attended private chambers than in government hospitals (p